2007
DOI: 10.3748/wjg.v13.i19.2697
|View full text |Cite
|
Sign up to set email alerts
|

NAT2polymorphism in Omani gastric cancer patients-risk predisposition and clinicopathological associations

Abstract: AIM:To study whether N-acetyltransferase 2 (NAT2 ) genotypes and phenotypes are associated with increased risk factor for gastric cancer in Omani patients and to study the clinico-pathological correlations and the prognostic significance of NAT2 . control subjects. NAT2 genotyping was performed using DNA sequencing. The prognostic significance of NAT2 and other clinicopathological features was assessed by univariate and multivariate analyses. M E T H O D S : RESULTS:We observed no significant association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The locus mutation directly caused to change activity of metabolic enzyme, which affected the metabolism of some drugs and carcinogens inactivation or activation and made incidence of cancer increase or decrease. Although, the markedly association between NAT2 rs1799930 and rs1799931 polymorphism and cancer risk was found in some publications (Majumdar et al, 2008;Zanrosso et al, 2012), while some other studies indicated that rs1799930 and rs1799931 had no any correlation with the risk of cancer (Gemignani et al, 2007;Al-Moundhri et al, 2007). In order to resolve this contradiction, we performed a meta-analysis involving in 21 eligible studies to understand if the rs1799930 and rs1799931 polymorphism were significantly associated with risk of cancer in ethnicity, types of cancer and source of controls.…”
Section: Discussionmentioning
confidence: 93%
“…The locus mutation directly caused to change activity of metabolic enzyme, which affected the metabolism of some drugs and carcinogens inactivation or activation and made incidence of cancer increase or decrease. Although, the markedly association between NAT2 rs1799930 and rs1799931 polymorphism and cancer risk was found in some publications (Majumdar et al, 2008;Zanrosso et al, 2012), while some other studies indicated that rs1799930 and rs1799931 had no any correlation with the risk of cancer (Gemignani et al, 2007;Al-Moundhri et al, 2007). In order to resolve this contradiction, we performed a meta-analysis involving in 21 eligible studies to understand if the rs1799930 and rs1799931 polymorphism were significantly associated with risk of cancer in ethnicity, types of cancer and source of controls.…”
Section: Discussionmentioning
confidence: 93%
“…[29, 31] However, we were unable to identify previous reports of NAT2 polymorphisms and survival in OOSCC, and NAT2 is not strongly associated with survival in other cancers. [23, 24, 32–35] Our positive finding for NAT2 might be explained by an improved prediction of NAT2 phenotype based on the use of thirteen SNPs. [20] The biological mechanism through which NAT2 might affect survival is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Briefly, our analysis focused on polymorphisms in eight genes associated with survival in cancers other than OOSCC ( mEH [21], MPO [22], NAT2 [23],[24]), or genes with biologically plausible associations with OOSCC survival through metabolism of polycyclic aromatic hydrocarbons (PAHs) or ethanol ( mEH [7] , MPO [25] , NAT2 [9], CYP1A1 and CYP2E1 [4, 26]), or OOSCC chemotherapies ( GSTM1 , GSTT1 , and GSTP1 [8, 27, 28]).…”
Section: Methodsmentioning
confidence: 99%
“…Active NAT1 overexpression was shown to enhance cell growth and etoposide resistance [38], and NAT1 genotype was found to be associated with the risk of relapse or death among children with neuroblastoma [39]. Although expression of NAT2 was recently found to alter the toxicity of CB1954, the component of an attractive therapy for tumor treatment [40], NAT2 polymorphism studies among patients with breast cancer [41], gastric cancer [42] and colorectal cancer [43] did not find any prognostic significance. Our study in NHL patients was the first one that observed NAT2 polymorphisms’ prognostic effects in cancer patients.…”
Section: Discussionmentioning
confidence: 99%